ALIS H ER NAVAI'S OPINIONS ON A JUST STATE AND RULER (Web of Teachers: Inderscience Research, 2025)
This article is about the concepts of a just state and ruler, as expressed in the works of Alisher Navoi, and their social and spiritual significance. Navoi interpreted justice as the main principle of state governance and social development. In his works, he emphasizes that the task of a ruler is not only to control power and authority, but also to serve the people and protect their justice. In creating the image of a just ruler, Navoi puts forward the concept of state governance based on religion, morality and human values. The article analyzes the compatibility of Navoi's ideas about a just state with modern principles of governance and their relevance for today's society